미래의 농수산물 유통전망 및 사이버거래소 설립방안 연구 - 이용선 (한국농촌경제연구원, 2008)
This study has the purpose of analyzing the need and roles of a cyber trading center for agricultural and fishery products; drawing up the measures to establish and operate the center; and developing a plan to build information system of the center. The study is largely divided into four sections: First of all, it highlights the need of a cyber center for agricultural and fishery products based on the analysis of agricultural and fishery product distribution status, and explains the roles and functions of the center. Secondly, it reviews the major business areas (types) of the cyber center, primary trading items and trading parties, operating entity, the initial plan to launch the center, the plan to control logistics and product quality, dispute resolution measures, price payment and clearing measures and legal and institutional stimulants for center operation. Thirdly, it develops a plan to build the Internet-based information system of the cyber trading center. Lastly, the economic effect and feasibility of building and operating a cyber trading center is analyzed. The key findings of the study are summarized as below: (1) Currently, the cyber trading of agricultural and fishery products is conducted centered around Business to Consumer (B2C), and Business to Business (B2B) trading is very rare. (2) The trading volume is getting larger along with the growing size and stratification of agricultural production and shipping organizations and the restaurants which are growing their size and building a chain. In addition, with the payment and guarantee systems prevailing and the logistical standardization in progress, the conditions for B2B trading are getting mature. (3) The government should take the initiative in establishing the cyber trading center to build the infrastructure for agricultural B2B trading which is difficult to be pursued by the private sector and to operate the trading system to encourage the private sector’s participation in it. It needs to build the differentiated information system for environmental friendly agricultural products and premium agricultural/fishery products to which securing marketing channel and building consumer trust is necessary to facilitate B2C transactions. (4) When organizing the cyber trading center, it could be established in the form of a special corporation or a subordinate (spin-off) organization under the management of a specialized agricultural and fishery distributor. It seems desirable to run the cyber center as a subordinate arm of an agricultural/fishery distribution organization for a time being due to the benefit of easy establishment and securing trust and later convert it into a special corporation when related laws are enacted. (5) Before having self-sustaining participants in the B2B transactions, the existing transactions of some volume should be transferred to the cyber trading center for B2B transaction. The B2B transactions don’t restrict the types of items for trading in principle, but in the pilot stage, more standardized items should be primarily introduced for trading. (6) To address difficulty facing small and mid-sized agricultural and fishery product purchasers when seeking a credit guarantee and thereby to facilitate B2B transactions, it is necessary to establish a ‘clearing house.’ (7) If a cyber trading center is up and running, several economic effects would result. Sellers could minimize financial impact coming from non-performing loans by applying the safe payment method. They can also expand sales routes and managerial efficiency. Purchasers can have the opportunity to expand their business (size growth) or improve managerial efficiency through the enlarged supply of funds. The cyber trading center could enhance trading transparency by supplying sufficient information and increase distributional efficiency by improving the trading structure over the mid to long term.